The Ladies of Ivy Cottage - Klassen, Julie 1964- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2017)
"Living with the two Miss Groves in Ivy Cottage, impoverished gentlewoman Rachel Ashford is determined to earn her own livelihood-- somehow. When the village women encourage her to open a subscription library with the many books she has inherited or acquired through donations, Rachel discovers two mysteries hidden among them. A man who once broke her heart helps her search for clues, but will both find more than they bargained for?"--Amazon.com.
Keywords: Man-woman relationships -- Fiction; Cottages -- Fiction; Subscription libraries -- Fiction; Hotelkeepers -- Fiction; Girls' schools -- Fiction; Wiltshire (England) -- Fiction -- Social life and customs -- 19th century; Christian fiction; Romance fiction